FORMULATION OF RIZATRIPTAN BENZOATE SUBLINGUAL TABLETS PREPARED BY DIRECT COMPRESSION WITH DIFFERENT BIOADHESIVE POLYMER: IN VITRO AND EX VIVO EVALUATION - Singh, Harmanpreet; Jaiswal, Pooja; Gupta, Suksham; Singh, Simerjit (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The current investigation deals with formulation and evaluation of fast disintegrating sublingual tablets of rizatriptan benzoate (RTB) to produce its intended therapeutic effect for acute treatment of migraine. When the drug is given by sublingual route, it overcomes the first pass metabolism and quick entry of drug in systemic circulation is obtained. It would result in fast pharmacological response hence faster relief from migraine which is an important criterion in migraine therapy. Methods: In this study, RTB sublingual tablets were prepared using direct compression process using various bioadhesive polymers such as sodium carboxymethyl cellulose, hydroxyl propyl methyl cellulose-K4M, and chitosan at various concentration ranging 0.5-5% w/w along with sodium starch glycolate (SSG) or cross carmellose sodium (CCS) as super disintegrants at different concentration ranging 2-8% w/w. Results: The tablets disintegrated quickly and dissolution tests conclude that RTB was released from the formulation within the compendial limits. The formulations batches (A8 and B8) containing 2% w/w chitosan along with 2% w/w SSG or CCS which disintegrate rapidly and show high dissolution and ex vivo permeation were selected as optimized formulations. Conclusion: The results obtained from the study showed that the bioavailability problem of the drug has been solved as the drug is given by sublingual route and it directly enters into systemic circulation. Furthermore, the formulation overcomes the problems associated with migraine attack as fast disintegrating technology is used.